RELEVANT ISSUES OF THE USE OF NON-PRICE CRITERIA IN THE PUBLIC PROCUREMENT SYSTEM OF UKRAINE - Syzov, A.; Artiushenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
This article analyzes the main aspects of the organization of procurement by managers of budget funds in Ukraine. Public procurement legislation obliges the public sector to carry out public large-scale procurement using procurement procedures under conditions that ensure optimal competition. In this context, the regulatory tools are disclosure requirements, different types of procedures for different types of contracts, requirements regarding the types of criteria and specifications to be applied during the procedure, as well as guarantees of the possibility of challenging the results of such procedures. The reform of the public procurement system is considered as one of the most successful reforms carried out in Ukraine recently. The determining factor in the selection of the procurement winner is the evaluation of tender proposals based on price and non-price criteria, taking into account the specifics of the procurement subject. Non-price criteria are important because they allow you to choose an offer that not only has the lowest price, but also provides additional benefits for the customer. Analyzing the trends of purchasing activities in European countries, it was established that the average percentage of purchases using non-price criteria to the total amount is 40.7 %, and in individual countries it even reaches 82 %. After studying the data on purchases made in Ukraine in 2016-2020, it was established that for Ukraine this ratio is on average less than 1 %, only in individual years it exceeds 1 %, which is in line with the trends in the development of the global procurement market and the best global practices. Analyzing the practice of European countries in the field of procurement, several approaches for determination of the weight of nonexchange criteria when calculating the procurement winner were analyzed. Also, on the basis of a survey conducted by the Ministry of Economic Development among customers in 2020, a number of problematic issues were identified that prevent most customers from fully using non-price criteria when making purchases. As a result of the study, the non-price criteria used by customers in Ukraine were summarized, as well as issues that require further research were listed to ensure effective and prompt reform of the procurement system in Ukraine with the standards of the European Union, the introduction of modern scientifically based approaches in the selection of suppliers and, as a result, increasing the effectiveness of the use of the state’s financial resources, both its own and obtained through borrowing from other countries, communities, and organizations.